Glass cloth, surface-treated glass cloth, prepreg, and printed circuit board
A glass cloth with controlled SD and RA values, treated with a coupling agent, addresses the issue of microvoids and fiber weave effects, ensuring high yield and signal speed in printed circuit boards.
Patent Information
- Application Number
- JP2024085949
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-05
- Filing Date
- 2024-05-28
- Publication Date
- 2024-12-17
AI Technical Summary
The challenge lies in achieving a good degree of fiber opening and uniformity in glass cloth to prevent microvoids, which cause warpage and reduce yield rates in printed circuit boards, while maintaining high signal transmission speed.
A glass cloth with an average unit area spreading coefficient (SD) of 0.35 to 0.75 and an average unit area uniformity coefficient (RA) of 0.10 to 0.40, with an RA/SD ratio of 0.10 to 1.10, treated with a coupling agent to enhance fiber spreading uniformity, is used to produce prepreg with no microvoids.
The solution results in prepreg with a good appearance and high yield rate, and printed circuit boards with high signal transmission speed, free from microvoids.
Smart Images

Figure 2024174826000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to textile fabrics, and in particular to glass cloth and its applications. [Background technology]
[0002] As electronic products move in the direction of more functionality, faster transmission, lighter weight and smaller size, the glass cloth used in manufacturing printed circuit boards (PCB) is being developed to be thinner.
[0003] In order to make the glass cloth thinner, it is common to manufacture the glass cloth by weaving glass fiber yarns having a short average filament diameter as warp and weft yarns, but this increases the proportion of the area of the yarn window (i.e., the gap between the warp and weft yarns in the glass cloth) in the glass cloth.
[0004] If the proportion of the yarn window area becomes high, a fiber weave effect is likely to occur when a signal passes through a printed circuit board made of such glass cloth, adversely affecting the signal transmission speed.
[0005] In order to solve the above problems, it is common to increase the degree of fiber opening (fiber splitting) of glass cloth. Fiber opening is a technology that increases the surface area of glass fiber yarn and reduces the yarn window by uniformly dispersing multiple filaments that make up the glass fiber yarn so that they are flat.
[0006] For example, Patent Documents 1 and 2 disclose glass cloths having a specific degree of fiber opening. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Taiwan Patent No. I720996 [Patent Document 2] Taiwan Patent No. I723117 Summary of the Invention [Problem to be solved by the invention]
[0008] However, if the glass cloth only meets a certain degree of spreading and the spreading uniformity is poor, i.e., if the difference in size of each yarn window in the glass cloth is too large, microvoids will exist in the prepreg manufactured using that glass cloth, and there will be a problem that the volumetric expansion and contraction of the prepreg will change too much during the manufacturing process of the printed circuit board, causing warping of the manufactured printed circuit board and reducing the yield rate of the printed circuit board.
[0009] SUMMARY OF THE PRESENT DISCLOSURE Accordingly, an object of the present invention is to provide a glass cloth, a surface-treated glass cloth, a prepreg, and a printed circuit board that have a good degree of spreading and good spreading uniformity. [Means for solving the problem]
[0010] In order to achieve the above object, the present invention provides a glass cloth which is a fabric woven from a plurality of warp yarns which are glass fiber yarns and a plurality of weft yarns which are glass fiber yarns, The glass cloth has an average unit area spread coefficient SD in the range of 0.35 to 0.75, an average unit area uniformity coefficient RA in the range of 0.10 to 0.40, and a value of RA / SD in the range of 0.10 to 1.10; The SD and the RA are determined by the following Equations 1 and 2:
[0011]
number
[0012] The present invention also relates to a surface-treated glass cloth which is a product of surface treatment of the above-mentioned glass cloth with a treatment liquid, The present invention provides a surface-treated glass cloth, characterized in that the treatment liquid contains a treatment agent selected from the group consisting of an aminosilane coupling agent, an alkenylsilane coupling agent, an acryloyloxysilane coupling agent, and combinations thereof.
[0013] The present invention also provides a prepreg comprising a partially solidified resin and the above-mentioned surface-treated glass cloth.
[0014] The present invention also provides a printed circuit board made of the above prepreg. Effect of the Invention
[0015] The glass cloth of the present invention has a good degree of spreading and good spreading uniformity, as designed by the inventors in consideration of the average width, average weaving density and width range of a plurality of warp threads and a plurality of weft threads, and the SD is limited to be within the range of 0.35 to 0.75, the RA is limited to be within the range of 0.10 to 0.40, and the value of RA / SD is limited to be within the range of 0.10 to 1.10. Thus, the surface-treated glass cloth of the present invention made from the glass cloth of the present invention also has a good degree of spreading and good spreading uniformity, and therefore the prepreg of the present invention made from the surface-treated glass cloth of the present invention has a good appearance and is free of microvoids, and the printed circuit board of the present invention made from the prepreg of the present invention has the advantages of a high yield rate and a high signal transmission speed. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a diagram showing a portion of an embodiment of a glass cloth of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] In order to more clearly describe the objectives, technical means and advantages of the embodiments of the present invention, the following will clearly and completely describe the technical means in the embodiments of the present invention in combination with the accompanying drawings of the embodiments of the present invention. It is clear that the described embodiments are only some embodiments of the present invention, and not all embodiments. Generally, the components of the embodiments of the present invention depicted and shown in the accompanying drawings can be arranged and designed in various different configurations. Therefore, the detailed description of the embodiments of the present invention provided below in the accompanying drawings does not constitute any limitation on the protection scope of the present invention, but only represents selected embodiments of the present invention.
[0018] In describing the present invention, terms indicating orientations and positional relationships, such as "upper," "lower," "inner," "outer," "left," "right," "front," and "rear," are based on the orientations and positional relationships shown in the drawings or the orientations and positional relationships customarily assumed when using the product of the present invention, for the purpose of easier and clearer description, and are not intended to teach or suggest that the corresponding apparatus or device has a specific orientation, a structure or operation in a specific orientation, etc., and are not intended to be limitations on the present invention.
[0019] <Glass cloth> The glass cloth of the present invention is a glass cloth woven from a plurality of warp yarns which are glass fiber yarns and a plurality of weft yarns which are glass fiber yarns. That is, the glass cloth of the present invention is a glass cloth produced by weaving a plurality of warp yarns which are glass fiber yarns and a plurality of weft yarns which are the glass fiber yarns.
[0020] In this embodiment, the glass fiber yarns used for the warp and weft are the same type of glass fiber yarn.
[0021] The glass cloth has an average unit area spreading coefficient SD in the range of 0.35 to 0.75, an average unit area uniformity coefficient RA in the range of 0.10 to 0.40, and a value of RA / SD in the range of 0.10 to 1.10.
[0022] SD and RA are determined by the following Equations 1 and 2.
[0023]
number
[0024] The average unit area opening coefficient SD represents the "degree of opening" of the glass cloth.
[0025] Moreover, W×F represents the average area of the portion where a plurality of warp threads and a plurality of weft threads overlap.
[0026] 25400 is a unit of weaving density (25.4 mm / threads = 25400 μm / threads) and represents the maximum width that can be assigned to each warp thread and each weft thread.
[0027]
number
[0028] The maximum area includes the area of the overlapping portions of each warp thread and each weft thread (i.e., the area of area A shown in Figure 1), the area of the portions of each warp thread that do not overlap with each weft thread (i.e., the area of area B shown in Figure 1), the area of the portions of each weft thread that do not overlap with each warp thread (i.e., the area of area C shown in Figure 1), and the area of each thread window (i.e., the area of area D shown in Figure 1).
[0029] The average unit area uniformity coefficient RA represents the "spread uniformity" of the glass cloth.
[0030]
number
[0031]
number
[0032]
number
[0033] By controlling the values of SD, RA and RA / SD within the above ranges, the glass cloth has a good degree of spreading and good spreading uniformity, i.e., the proportion of the yarn window area is low and the difference in size of each yarn window in the glass cloth is small, and therefore the surface-treated glass cloth of the present invention produced using the glass cloth (i.e., the glass cloth of the present invention) also has a good degree of spreading and good spreading uniformity, and therefore the prepreg of the present invention produced using the surface-treated glass cloth of the present invention has a good appearance and is free of microvoids, and the printed circuit board of the present invention produced using the prepreg of the present invention has the advantages of a high yield rate and a high signal transmission speed.
[0034] If the SD is less than 0.35, the degree of fiber opening of the glass cloth is low, i.e., the proportion of the yarn window area is high, and when a signal passes through a printed circuit board manufactured using such a glass cloth, a fiber weaving effect is likely to occur, which has an adverse effect on the signal transmission speed.
[0035] Generally, in order to improve the degree of opening of glass cloth, the water pressure used for opening when manufacturing the glass cloth is increased accordingly. When SD exceeds 0.75, the degree of opening of the glass cloth is high. However, since the water pressure used for opening multiple warp threads and multiple weft threads in the glass cloth is too high and filaments may break, the manufactured glass cloth has a defect of having fuzz on the surface. A prepreg manufactured using such a glass cloth has a defect of having colloidal particles. A printed circuit board manufactured using such a prepreg has a defect of having protrusions.
[0036] If the RA exceeds 0.40, the uniformity of the glass cloth spread is poor, i.e., the difference in size of each yarn window in the glass cloth is large. Therefore, the prepreg manufactured using such a glass cloth has microvoids, and there is a problem that the volumetric expansion and contraction of the prepreg changes too much during the manufacturing process of the printed circuit board, so that the manufactured printed circuit board warps and the yield rate of the printed circuit board decreases.
[0037] When the RA / SD value exceeds 1.10, even if the SD is within the range of 0.35 to 0.75 and the RA is within the range of 0.10 to 0.40, the prepreg produced using such a glass cloth has a poor appearance and contains microvoids, and the printed circuit board produced using such a prepreg has a low yield rate.
[0038] To provide a prepreg with a better appearance, in some embodiments, the RA / SD value is in the range of 0.20 to 1.00, and in some embodiments, the RA / SD value is in the range of 0.20 to 0.90.
[0039] In some embodiments, each warp thread is made of multiple filaments and each weft thread is made of multiple filaments, each warp thread has an average filament diameter in the range of 3.0 μm to 5.0 μm and an average filament number in the range of 30 to 200, and each weft thread has an average filament diameter in the range of 3.0 μm to 5.0 μm and an average filament number in the range of 30 to 200.
[0040] Each filament is produced by spinning a glass raw material. The glass raw material may be, for example, a glass raw material for general electronic components (e.g., E-glass), a low dielectric constant (low K) glass raw material, a low thermal expansion coefficient (low CTE) glass raw material, or a glass raw material having both a low dielectric constant and a low thermal expansion coefficient.
[0041] In some embodiments, the average thickness of the glass cloth is in the range of 10.0 μm to 50.0 μm, and the average basis weight of the glass cloth is 10.0 g / m 2 ~50.0g / m 2 is within the range.
[0042] In some embodiments, the average weave density of the multiple warp yarns is within a range of 50 / 25.4 mm to 100 / 25.4 mm, and the average weave density of the multiple weft yarns is within a range of 50 / 25.4 mm to 100 / 25.4 mm, based on the average area of the glass cloth as the calculation basis.
[0043] The glass cloth of the present invention is produced by treating an unopened glass cloth (i.e., a glass cloth that has not been opened) with a process including an opening treatment. As long as the produced glass cloth has an SD in the range of 0.35 to 0.75, an RA in the range of 0.10 to 0.40, and an RA / SD value in the range of 0.10 to 1.10, any existing operation method and equipment for the opening treatment are suitable for producing the glass cloth of the present invention, and there is no need to limit the specific operation method and equipment for the opening treatment.
[0044] In some embodiments, the opening process is performed by applying tension to the unopened glass cloth while spraying a high-pressure water column onto the unopened glass cloth using a spreading device. The tension is, for example, but not limited to, in the range of 50 N to 300 N, and the water pressure of the high-pressure water column is, for example, but not limited to, in the range of 20 kg to 80 kg.
[0045] <Surface-treated glass cloth> The surface-treated glass cloth of the present invention is a product of surface treatment of the above-mentioned glass cloth of the present invention with a treatment liquid. That is, the surface-treated glass cloth of the present invention is produced by surface-treating the above-mentioned glass cloth, and the surface treatment includes reacting the glass cloth with a treatment liquid to change the properties of the glass cloth so that the surface-treated glass cloth can react with a resin in a subsequent process.
[0046] The glass cloth of the present invention has the advantages of having a good degree of spreading and good uniformity of spreading, so that the surface-treated glass cloth of the present invention also has the advantages of having a good degree of spreading and good uniformity of spreading.
[0047] In some embodiments, the treatment liquid is made by containing a treatment agent selected from the group consisting of an aminosilane coupling agent (amino group-containing silane coupling agent), an alkenylsilane coupling agent (alkenyl group-containing silane coupling agent), an acryloyloxysilane coupling agent (acryloyloxy group-containing silane coupling agent), and combinations thereof. That is, the treatment liquid is made by containing a treatment agent.
[0048] Examples of the aminosilane coupling agent include, but are not limited to, 3-aminopropyltriethoxysilane.
[0049] Examples of alkenyl silane coupling agents include, but are not limited to, vinyltrimethoxysilane.
[0050] Examples of acryloyloxysilane coupling agents include, but are not limited to, 3-(trimethoxysilyl)propyl methacrylate.
[0051] In some embodiments, the amino silane coupling agent is 3-aminopropyltriethoxysilane, the alkenyl silane coupling agent is vinyltrimethoxysilane, and the acryloyloxy silane coupling agent is 3-(trimethoxysilyl)propyl methacrylate.
[0052] <Prepreg> The prepreg of the present invention contains a partially solidified resin and the above-mentioned surface-treated glass cloth of the present invention, that is, the prepreg of the present invention is formed by partially solidifying an impregnated fabric containing a resin and the above-mentioned surface-treated glass cloth of the present invention.
[0053] Specifically, the production of prepreg involves impregnating the surface-treated glass cloth of the present invention, which serves as both a reinforcement and an insulation material, with a resin to obtain an impregnated fabric, and then partially solidifying the impregnated fabric to reach a B-stage.
[0054] The surface-treated glass cloth of the present invention has the advantages of having a good degree of spreading and good spreading uniformity, i.e., the proportion of the yarn window area in the surface-treated glass cloth is low and the difference in size of each yarn window in the surface-treated glass cloth is small, so that the area filled with resin in the surface-treated glass cloth is relatively small, and the appearance of the prepreg of the present invention made from the surface-treated glass cloth of the present invention is good and no microvoids exist.
[0055] Examples of the resin include, but are not limited to, a thermosetting resin or a UV curable resin.
[0056] In some embodiments, the resin is a thermosetting resin.
[0057] Examples of the thermosetting resin include polyphenylene ether resin, phenol resin, epoxy resin, and urea resin. Examples of the resin include, but are not limited to, formaldehyde resin, unsaturated polyester resin, melamine resin, fluororesin, and bismaleimide triazine resin (abbreviated as BT resin).
[0058] Examples of the ultraviolet curing resin include, but are not limited to, ultraviolet curing polyurethane and ultraviolet curing acrylic resin.
[0059] In some embodiments, the thermosetting resin is, for example, one selected from the group consisting of epoxy resins, polyphenylene ether resins, phenolic resins, and bismaleimide triazine resins.
[0060] An example of a downstream application of the prepreg of the present invention is to produce a laminate by stacking a plurality of prepregs and then laminating a copper foil layer on at least one side of the laminate, and then subjecting the laminate to thermocompression bonding to produce a copper clad laminate (CCL).
[0061] In some embodiments, the manufacturing of the prepreg further includes adding an inorganic filler to manufacture an impregnated cloth, whereby the impregnated cloth is partially solidified to form a prepreg further comprising an inorganic filler. By adding an inorganic filler, it is possible to adjust properties such as thermal conductivity, laser drilling property, and thermal expansion of a copper clad laminate manufactured using the prepreg, and thus a printed circuit board manufactured using the copper clad laminate has good reliability.
[0062] <Printed circuit board> The printed circuit board of the present invention is made of the prepreg of the present invention, that is, the printed circuit board of the present invention is manufactured by using the prepreg of the present invention.
[0063] Specifically, downstream applications of the prepreg further include drilling, plating with gold or gold-containing alloys, and etching of circuit patterns on copper-clad laminates to produce printed circuit boards.
[0064] Since the prepreg of the present invention has a good appearance and is free of microvoids, the printed circuit board of the present invention produced using the prepreg of the present invention does not suffer from the problem of low yield rate.
[0065] Examples of the present invention will now be described, with the understanding that these examples are illustrative and explanatory and should not be construed as limiting the present invention.
[0066] <Example 1> Glass cloth manufacturing: A weaver's beam was obtained by sequentially performing warping and sizing and beaming processes on a plurality of glass fiber yarns as warp threads, and the weaver's beam was then installed on an air jet loom (manufacturer: Toyota Industries Corporation, model number: JAT710) and interwoven with a plurality of glass fiber yarns as weft threads to form an unspread glass cloth. The unspread glass cloth was then sequentially subjected to desizing and spreading processes to produce a glass cloth.
[0067] The specifications of the raw silk (gray yarn) of each warp yarn and each weft yarn (i.e., the average filament diameter and the average number of filaments), the tension applied in the opening process, and the water pressure of the high-pressure water column are shown in Table 1.
[0068] Manufacturing of surface-treated glass cloth: The glass cloth was immersed in the treatment solution for 30 seconds and then dried at 150° C. to produce a surface-treated glass cloth.
[0069] The treatment liquid was produced by subjecting an aminosilane coupling agent and an aqueous acetic acid solution to a hydrolysis reaction for 30 minutes at a pH value in the range of 3.5 to 5.5. The total amount of the aminosilane coupling agent and the aqueous acetic acid solution was 100 wt%, and the amount of the aminosilane coupling agent used was 0.08 wt%.
[0070] How prepreg is manufactured: The surface-treated glass cloth was impregnated with a resin solution to obtain an impregnated fabric, which was then cured at 210° C. for 6 minutes to produce a partially cured prepreg.
[0071] The resin solution was obtained by mixing a resin (specifically, bismaleimide triazine resin, manufacturer: Taiwan Prior Company Limited, model number: BT-0001) with a solvent (specifically, methyl ethyl ketone). The total amount of the resin solution was 100 wt%, and the amount of the resin used was 50 wt%.
[0072] <Examples 2 to 13 and Comparative Examples 1 to 7> The differences between Example 2 to Example 13 and Comparative Example 1 to Comparative Example 7 are shown in Tables 1 to 3. Warp yarns and weft yarns having different raw silk specifications were used under different opening treatment conditions to produce glass cloths having different opening degrees and different opening uniformities.
[0073] In the resin solutions used in Examples 2 to 13 and Comparative Examples 1 to 7, the resin was an epoxy resin (manufacturer: Nan Ya Plastics Corporation, Taiwan, model number: NPEB475 In the case of K70, the solvent was 1-methoxy-2-propanol, and the amount of resin used was 60 wt% based on the total amount of resin solution of 100 wt%, and the impregnated fabric was cured at 190°C for 6 min.
[0074] In the resin solutions used in Examples 2 to 13 and Comparative Examples 1 to 7, when the resin was a polyphenylene ether resin (manufacturer: Saudi SABIC, model number: NORYL SA9000), Correspondingly, the solvent was methyl ethyl ketone and the amount of resin used was 65 wt%, taking the total amount of resin solution as 100 wt%, and the impregnated fabric was cured at 180° C. for 4 min.
[0075] <Evaluation items> The following describes the method of measuring the specifications of the glass cloths and the method of measuring the specifications and evaluating the appearance of the prepregs in Examples 1 to 13 and Comparative Examples 1 to 7, taking Example 1 as an example. The measurement results and the appearance evaluation results are shown in Tables 1 to 3.
[0076] Average warp density (D w ), average weaving density of weft yarn (D f ) Measurement: The surface of the glass cloth of Example 1 was measured using a digital weave density measuring machine (manufacturer: Textest Instruments, Switzerland, model number: FX3250) to obtain the average weave density of the multiple warp threads and the average weave density of the multiple weft threads in the glass cloth of Example 1.
[0077] Measurement of the average warp width (W) and the average weft width (F): The glass cloth of Example 1 having a length of 30 cm was cut and the cut glass cloth was divided evenly into five measurement areas along the width direction. The cut glass cloth was placed under a microscope (manufacturer: NIKON, model number: ME600, magnification: 5x) and each measurement area was photographed to obtain five photographs, which were then measured using image dimension measurement software (TS-Link, TOTAL-SMART The width of each warp thread and the width of each weft thread in each photograph were measured using a measuring tape (manufactured by YAMAHA TECHNOLOGY CO., LTD.), and the average value of the multiple warp threads and the average value of the multiple weft threads in each photograph were calculated. Finally, the average value of the average width data measured in each measurement area (i.e., the average width data of five warp threads and the average width data of five weft threads) was calculated, thereby obtaining the average width of the multiple warp threads and the average width of the multiple weft threads in the glass cloth of Example 1.
[0078] Warp width range (R w ), weft width range (R f ) is calculated as follows: R w = The difference between the maximum and minimum widths among multiple warp threads. R f = The difference between the maximum and minimum widths among multiple weft threads.
[0079] Measurement of the average thickness of the glass cloth: The glass cloth of Example 1, which was 30 cm long and divided into five measurement areas, was placed on a digital micrometer (manufacturer: TESA, Switzerland, model number: MICROMASTER IP54, minimum scale: 0.001 mm) to measure the thickness of each measurement area, and finally, the average value of the thickness data measured in each measurement area (i.e., the five thickness data) was calculated to obtain the average thickness of the glass cloth of Example 1.
[0080] Measurement of average basis weight of glass cloth: The glass cloth of Example 1 was cut into three equal pieces, and each of the equal pieces was further cut into samples measuring 30 cm x 30 cm. The weight of each sample was measured using an electronic balance (manufacturer: OHAUS, USA, model number: PR224, minimum scale: 0.0001 g), and the basis weight of each sample was calculated using the following formula 3.
[0081] Equation 3: Sample basis weight = sample weight / sample area Finally, the average value of the basis weight of each sample (i.e., the data of the three basis weights) was calculated to obtain the average basis weight of the glass cloth of Example 1.
[0082] Determination of resin content in prepregs: According to the standard measurement method of "Resin Content of Prepreg Material (Treated Weight)" of IPC-TM-650 2.3.16.1 (1994 edition), the glass cloth of Example 1 and the prepreg of Example 1 were each cut into samples with a size of 20 cm x 20 cm. The weight of each sample was measured using the above electronic balance, and the resin content in the prepreg of Example 1 was calculated by the following Equation 4.
[0083] Equation 4: Resin content in prepreg = (1-weight of glass cloth sample / weight of prepreg sample) x 100% Measurement of the average thickness of the prepreg: A 30 cm length of the prepreg of Example 1 was cut out and the cut prepreg was equally divided into five measurement areas along the width direction. The cut prepreg was placed on the digital micrometer to measure the thickness of each measurement area. Finally, the average value of the thickness data measured in each measurement area (i.e., the five thickness data) was calculated to obtain the average thickness of the prepreg of Example 1.
[0084] Determining the number of microvoids in the prepreg and evaluating the appearance of the prepreg: The prepreg of Example 1 was cut into samples measuring 5 cm x 5 cm, which were then placed under the microscope and observed. Any pinhole-sized holes on the surface of the sample were considered to be microvoids, and the number of pinhole-like microvoids on the surface of the sample was calculated.
[0085] If the prepreg had 0 microvoids, the prepreg appearance was rated as "good", if the prepreg had 1-100 microvoids, the prepreg appearance was rated as "has a few pinholes", and if the prepreg had 101 or more microvoids, the prepreg appearance was rated as "has obvious pinholes".
[0086] [Table 1-1]
[0087] [Table 1-2]
[0088] [Table 2-1]
[0089] [Table 2-2]
[0090] [Table 3-1]
[0091] [Table 3-2] According to Tables 1 to 3, the glass cloths of Examples 1 to 13 satisfy all of the requirements of SD being in the range of 0.35 to 0.75, RA being in the range of 0.10 to 0.40, and RA / SD being in the range of 0.10 to 1.10, and the prepregs of Examples 1 to 13 have no microvoids on the surface and have a good appearance.
[0092] In contrast, the glass cloths of Comparative Examples 1 to 7 do not satisfy all of the requirements of SD being in the range of 0.35 to 0.75, RA being in the range of 0.10 to 0.40, and RA / SD value being in the range of 0.10 to 1.10, and the prepregs of Comparative Examples 1 to 7 have microvoids on the surface.
[0093] Therefore, it was proven that the glass cloths of Examples 1 to 13 satisfy all of the requirements of an SD in the range of 0.35 to 0.75, an RA in the range of 0.10 to 0.40, and an RA / SD value in the range of 0.10 to 1.10, thereby achieving the absence of microvoids on the surface of the prepregs of Examples 1 to 13.
[0094] According to the above, the glass cloth of the present invention has a good degree of spreading and good spreading uniformity by calculating SD and RA from the average width, average weaving density and width range of a plurality of warps and a plurality of wefts, and by restricting SD to be within the range of 0.35-0.75, RA to be within the range of 0.10-0.40 and the value of RA / SD to be within the range of 0.10-1.10, and the surface-treated glass cloth of the present invention produced using the glass cloth of the present invention also has a good degree of spreading and good spreading uniformity, so that the prepreg of the present invention produced using the surface-treated glass cloth of the present invention has a good appearance and is free of microvoids, and the printed circuit board of the present invention produced using the prepreg of the present invention has the advantages of a high yield rate and a high signal transmission speed. Thus, the object of the present invention can be reliably achieved.
[0095] While the invention has been described in connection with what are considered to be exemplary embodiments, it is understood that the invention is not limited to the disclosed embodiments, but is intended to cover various arrangements within the broadest spirit and scope so as to encompass all such modifications and equivalent arrangements.
[0096] The above embodiment is illustratively intended to explain the principles and effects of the present invention, and is not intended to limit the present invention. Those skilled in the art may make some changes or modifications to the above embodiment without departing from the spirit and scope of the present invention. Therefore, all changes and modifications made by those skilled in the art without departing from the gist of the present invention should be considered to be within the scope of protection of the present invention. [Industrial Applicability]
[0097] The glass cloth of the present invention is suitable for use in electronic products. [Explanation of symbols]
[0098] A: The area where each warp thread overlaps with each weft thread B Area of each warp thread that does not overlap with each weft thread C Area of each weft thread that is not overlapped with each warp thread D Area of each yarn window
Claims
1. A glass cloth is a fabric woven from a plurality of warp yarns which are glass fiber yarns and a plurality of weft yarns which are glass fiber yarns, The glass cloth has an average unit area spread coefficient SD in the range of 0.35 to 0.75, an average unit area uniformity coefficient RA in the range of 0.10 to 0.40, and a value of RA / SD in the range of 0.10 to 1.10; The SD and the RA are determined by the following Equations 1 and 2: [0010] Wherein W is the average width of the plurality of warp yarns, F is the average width of the plurality of weft yarns, D w is the average weave density of the plurality of warp yarns, D f is the average weaving density of the plurality of weft yarns, R w is the range of widths of the plurality of warp yarns, R f is a range of widths of the plurality of weft yarns.
2. 2. The glass cloth according to claim 1, wherein the RA / SD value is within a range of 0.20 to 1.
00.
3. 3. The glass cloth according to claim 2, wherein the RA / SD value is within a range of 0.20 to 0.
90.
4. Each of the warp yarns is composed of a plurality of filaments, Each of the weft yarns is composed of a plurality of filaments, Each of the warp yarns has an average filament diameter in the range of 3.0 μm to 5.0 μm and an average filament number in the range of 30 to 200, 2. The glass cloth according to claim 1, wherein each of the weft yarns has an average filament diameter in the range of 3.0 μm to 5.0 μm and an average number of filaments in the range of 30 to 200.
5. The average thickness of the glass cloth is in the range of 10.0 μm to 50.0 μm, The average basis weight of the glass cloth is 10.0 g / m 2 ~50.0g / m 2 is within the range of 2. The glass cloth according to claim 1, wherein, based on an average area of the glass cloth as a calculation basis, an average weave density of the plurality of warp yarns is within a range of 50 yarns / 25.4 mm to 100 yarns / 25.4 mm, and an average weave density of the plurality of weft yarns is within a range of 50 yarns / 25.4 mm to 100 yarns / 25.4 mm.
6. A surface-treated glass cloth which is a product of surface treatment of the glass cloth according to claim 1 with a treatment liquid, The treatment liquid comprises a treatment agent selected from the group consisting of an aminosilane coupling agent, an alkenylsilane coupling agent, an acryloyloxysilane coupling agent, and combinations thereof.
7. A prepreg comprising a partially solidified resin and the surface-treated glass cloth according to claim 6.
8. 8. The prepreg of claim 7, wherein the resin is a thermosetting resin.
9. 9. The prepreg of claim 8, wherein the thermosetting resin is selected from the group consisting of epoxy resins, polyphenylene ether resins, and bismaleimide triazine resins.
10. A printed circuit board, which is made of the prepreg according to any one of claims 7 to 9.
Citation Information
Patent Citations
Woven fabric of glass and laminate using the same
JP1995042045A
Woven glass fiber fabric for resin-reinforcement
JP1995157971A
Prepreg and its preparation
JP2008222986A
Glass cloth
JP2017043873A
Glass cloth
JP2018021274A
